THE EFFECT OF CUSTOMER RELATIONSHIP MANAGEMENT (CRM) AND BRAND IMAGE ON PURCHASING DECISIONS WITH SERVICE QUALITY AS AN INTERVENING VARIABLE (Study on Arung Senja Cafe Surabaya) - Fitria Rahmatul Laili; Yanda Bara Kusuma (Peneliti.net, 2026)
This study aims to determine the effect of Customer Relationship Management (CRM) and Brand Image on Purchase Decision through Service Quality as an intervening variable at Arung Senja Cafe Surabaya. The type of research used is explanatory research with a quantitative approach. The sampling technique used non-probability sampling with purposive sampling, involving 100 respondents who had made purchases at Arung Senja Cafe. Data were collected using questionnaires and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results show that Customer Relationship Management has a positive and significant effect on Service Quality (0.350) and Brand Image has a positive and significant effect on Service Quality (0.578). Meanwhile, Customer Relationship Management has a positive but not significant effect on Purchase Decision (0.098). Brand Image has a positive and significant effect on Purchase Decision (0.779). Furthermore, Service Quality has a positive but not significant effect on Purchase Decision (0.009). The mediation test results indicate that Service Quality does not mediate the relationship between Customer Relationship Management and Purchase Decision nor between Brand Image and Purchase Decision. Overall, Brand Image is the most dominant factor influencing Purchase Decision at Arung Senja Cafe.